Insecticide resistance in field populations of the pear psyllids Cacopsylla permixta and Cacopsylla bidens in Iran. (19th November 2021) - Esmaeily, Mojtaba; Talebi, Khalil; Hosseininaveh, Vahid; Nozari, Jamasb; Burckhardt, Daniel; Jackson, Colin J.; Oakeshott, John G.
Abstract: Cacopsylla permixta and Cacopsylla bidens are major pests of pears in Iran. They are commonly sprayed with various insecticides up to 12 times a year but control by these means is no longer reliable, suggesting the evolution of resistance. Here, we report about 60‐fold variation in diazinon susceptibility both among five geographic populations of C. bidens and among three geographic populations of C. permixta, as well as 12‐ to 14‐fold variations in imidacloprid susceptibility in these populations. The levels of resistance to the two compounds were highly correlated in the different populations. Esterase, cytochrome P450, and glutathione S ‐transferase activities all varied by about two‐fold among the different populations and were also highly correlated with population resistance to the two insecticides, implying differences in metabolism contribute to the differences in resistance. Bioassays with inhibitors of each class of enzyme indicated all three, but particularly the esterases, contributed to the variation in diazinon resistance, while esterase and, in particular, cytochrome P450 activities contributed to the variation in imidacloprid resistance. The most resistant populations of each species also showed some resistance to chlorpyrifos and acetamiprid, suggesting there may be wide cross resistance to organophosphates and neonicotinoids in these populations. The sampled psyllid populations showed lower levels of resistance to representatives of two other classes of insecticides currently used in Iran, spirotetramat and abamectin, though resistance to spirotetramat was detectable and was correlated with diazinon and imidacloprid resistance across populations. We conclude that metabolic resistance to a range of insecticides is now evolving in field populations of both species in Iran, warranting timely development of resistance management plans. Abstract : Our results showed that high diazinon, low imidacloprid, and very low level of chlorpyrifos, acetamiprid, and spirotetramat resistances have evolved in some field populations of the two pear psyllid species in Iran. The relationship between detoxification enzyme activity and diazinon and imidacloprid resistance suggests a role for are metabolism in resistance, although some contribution from genetic variants affecting other mechanisms cannot be ruled out. Bioassays with inhibitors of each class of enzyme indicated all three (esterases, cytochrome P450, and glutathione S ‐transferase), but particularly the esterases, contributed to the variation in diazinon resistance, while esterase and, in particular, cytochrome P450 activities contributed to the variation in imidacloprid resistance.